2008
DOI: 10.1007/s11199-008-9544-x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Roles and Empathic Accuracy: The Role of Communion in Reading Minds

Abstract: Although empathic accuracy is considered a stable skill, few individual difference measures consistently predict performance on Ickes' (e.g., 2001) empathic accuracy measure. Because past work has shown that women are more empathically accurate than men when female gender roles are made salient before an empathic accuracy task, we hypothesized that self-reported communion and related variables might predict empathic accuracy. Participants (194 undergraduates) from a northwestern U.S. university completed an em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(33 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…Women have long been considered more empathetic than men (4,5). Compared to men, women are more likely to have higher scores on PD and EC, while gender differences on PT and FS scores have not been observed (14,15). Our findings partially confirmed previous findings of high scores on EC in female participants.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Women have long been considered more empathetic than men (4,5). Compared to men, women are more likely to have higher scores on PD and EC, while gender differences on PT and FS scores have not been observed (14,15). Our findings partially confirmed previous findings of high scores on EC in female participants.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, some clinical features, such as the presence of psychotic mood episodes and suicide attempts, may cause different disease courses in depressed subjects. In addition, the relationship between empathy and gender in patients with MDD is unclear, although the presence of this relationship in non-depressed people is most consistently supported by various studies (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Wheeler et al (2002) also found that empathy mediated this interaction so that the combined effect of hostile masculinity and impersonal sexuality on sexual aggression was less pronounced in men with high empathy than those with low empathy. Given the functional relationship between nurturance and empathy (Karniol, Gabay, Ochion, & Harari, 1998;Laurent & Hodges, 2009), this result indirectly corroborates the assumption that nurturance is a protective factor against sexual aggression.…”
Section: Introductionsupporting
confidence: 73%
“…For example, it was proposed that women are better judges of another person's personality because they are more empathic (cf. Klein & Hedges, ; Laurent & Hodges, ; Lippa & Dietz, ). Although plausible, the gender of judges is irrelevant in achieving agreement between self‐ and other‐ratings: Women are not more accurate than men (Allik et al, ).…”
Section: Good Judgesmentioning
confidence: 99%